Software para definição e avaliação de unidades de manejo em agricultura de precisão - Bazzi, Claudio Leones (2011)
Water and soil conservation is essential for water resources management. Thus, conservationist actions are developed and applied in order to make part of a set of measures which enable the supply management, based on an appropriate recharge of the aquifers as well as the improvement of their quality, from the reduction of erosive processes and volume of effluents discharged in lakes and rivers. Some of these actions are associated to the precision agriculture, which aims at improving yield, reducing costs as well as the environmental impact by a site-specific management in an agricultural area. Thus, the main goal of this research is the development of software to determine the management zones, using empirical and grouping methods to be applied for soil and water conservation. This software tool, multiplatform, provides the ability to input and output data through specific standards, draws thematic maps according to well-known methods of interpolation (inverse of distance, moving average and the nearest neighbor) As well as evaluates management zones, generated by methods of relative efficiency and comparison test of averages. The software was tested according to physical and chemical data and soybean yield, so that management zones were generated and evaluated. Water leaching data were analyzed if the management zones can be used to identify the places with the greatest potential for leaching. The use of software allowed the generation of management zones in an easier way, as well as their analyses. Therefore, it identified that the generated management zones could be used as a source of recommendation and analysis of most of the studied attributes. Except nitrogen, the other attributes had the same potential for leaching, according to the comparison test of straight lines